Manajemen Perencanaan Pendidikan untuk Program Bimbingan Membaca dan Tahfidz Al-Qur’an Peserta Didik - Damri; Indra Prasetyo, Yudo; Asmendri; Sari, Milya (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
Educational planning is a fundamental component in achieving the goals of educational institutions, including at SMA Negeri 3 Padang Panjang. One of the key programs that plays a role in shaping students' character and moral integrity is the guidance program for reading and memorizing the Qur’an. This program not only aims to develop technical skills in reading the Qur’an but also to instill spiritual values that can shape the morality of the younger generation. With a total of 862 students, 18.56% of whom are non-Muslim, SMA Negeri 3 Padang Panjang has implemented this program with an inclusive approach. This study aims to examine the management of the planning system for the guidance program on Qur’an reading and memorization, from the planning stage, implementation, to evaluation. Using descriptive qualitative research methods through observation, interviews, and documentation, this research seeks to comprehensively describe the planning and management process of the guidance program. The findings of this study are expected to provide new insights and recommendations for other schools in managing Qur’anic guidance programs effectively and efficiently.